Like Virginity, Once Lost : Five views on Nordic art now - Birnbaum, Danïel; Larsen, Lars Bang; Blom, Ina; Valjakka, Timo; Nilsson, John Peter; Arrhenius, Sara ([S.l.] : Propexus, 1999)
Ahtila, Eija-Lisa ; Andersson, Asa ; Baselitz, Georg ; Bergström, Lars ; Bigert, Mats ; Billgren, Ernst ; Bosch, Hieronymus ; Brinch, Jes ; Bäckström, Miriam ; Bärtas, Magnus ; Dolven, A.K. ; Dragset, Ingar ; Duchamp, Marcel ; Ekman, Marie-Louise ; Elggren, Leif ; Eliasson, Olafur ; et al.
Like Virginity, Once Lost is an introduction to the Nordic art situation at the end of the 90s.
boek
Keywords: Scandinavië